1999
DOI: 10.1097/00007890-199909150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cryopreservation on in Vitro and in Vivo Long-Term Function of Human Islets1

Abstract: These findings showed that cryopreservation affects the function of isolated human islets, maintaining in vivo function for a limited period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 50 publications
2
11
2
Order By: Relevance
“…The reduced insulin release on day 21 may be attributed to inappropriate culture conditions. Piemonti et al reported the loss of b cell function in cryopreserved islets Improvement of Human Islet Cryopreservation by a p38 MAPK Inhibitor within three months (44). We did not observe the decline of b cell function following transplantation.…”
Section: Omori Et Alcontrasting
confidence: 69%
“…The reduced insulin release on day 21 may be attributed to inappropriate culture conditions. Piemonti et al reported the loss of b cell function in cryopreserved islets Improvement of Human Islet Cryopreservation by a p38 MAPK Inhibitor within three months (44). We did not observe the decline of b cell function following transplantation.…”
Section: Omori Et Alcontrasting
confidence: 69%
“…Interestingly, human and porcine islets with higher levels of insulin secretion at both the basal level and stimulated level of glucose stimulation were less likely to reverse diabetes in nude mouse transplantations, whereas a 100% cure rate was achieved by NHP islets. If islets release high amount of insulin at basal stimulus indicates unhealthy status of islets (6-8). …”
Section: Resultsmentioning
confidence: 99%
“…The islets (250 islet/ml) were cultured freeEvaluation of Graft Function floating (37°C, 5% CO 2 ) in RPMI-1640 medium (BioWhittaker, Walkersville, MD, USA) supplemented with Blood sugar levels were measured 15, 30, and 60 min L-glutamine (Sigma), penicillin and streptomycin (1000 after the end of surgical procedure, daily for the first U/ml and 10 mg/ml; Sigma), and 10% (v/v) fetal calf week and then every second day posttransplantation. serum (HyClone, Celbio, Logan, UT, USA) for [20][21][22][23][24] Surgical death was defined as death within the first 7 h before the transplant. Islet purity was >90%.…”
Section: Methodsmentioning
confidence: 99%